A literature review of the Ophiuroidea (Echinodermata) from the Pacific coast of Mexico - Granja-Fernández, Rebeca (2015)
Despite the important effort of knowing the Ophiuroidea diversity in the Mexican Pacific, some mistakes in the taxonomic nomenclature have pervaded through time. In order to clarify the latter, a checklist based on literature review of brittle stars from the Mexican Pacific is provided. We reviewed a total of 105 references that in total summarized 125 species of brittle stars from the Mexican Pacific (112) and the Gulf of California (97), belonging to two orders, 16 families and 50 genera. These records are higher than those reported on previous studies carried out in the area. México is the country with the highest number of brittle stars reported in the Tropical Eastern Pacific; this may be due to its exceptional oceanographic conditions, location and coastline extension. However, a total of 27 species reported in the literature were considered doubtful due to their general distributions and were not included in the checklist. Of the reported species, 35 have their type locality in the Mexican Pacific, corroborating the importance of the country in the Tropical Eastern Pacific in terms of Echinodermata diversity